2021
DOI: 10.3390/fractalfract5040164
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Analysis on Pore Structure and Hydration of Magnesium Oxysulfate Cements by First Principle, Thermodynamic and Microstructure-Based Methods

Abstract: Magnesium oxysulfate (MOS) cement is a typical eco-friendly cementitious material, which presents excellent performances. In this work, a novel multiscale modeling strategy is proposed to simulate the hydration and pore structure of MOS cement system. This work collected and evaluated the Gibbs free energy of formation for main hydrates and equilibrium constant of main reactions in MOS cement system based on a first principle calculation using Material Studio. Followingly, the equilibrium phase compositions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 123 publications
(47 citation statements)
references
References 61 publications
0
47
0
Order By: Relevance
“…Fractal theory is a new method of mathematics, resolving the irregularities in nature [67][68][69][70]. Many researchers [71][72][73][74][75][76][77][78] demonstrated that fractal theory links microstructures with the macro-performance of cement-based materials well, and vice versa.…”
Section: Fractal Dimension Calculationmentioning
confidence: 99%
“…Fractal theory is a new method of mathematics, resolving the irregularities in nature [67][68][69][70]. Many researchers [71][72][73][74][75][76][77][78] demonstrated that fractal theory links microstructures with the macro-performance of cement-based materials well, and vice versa.…”
Section: Fractal Dimension Calculationmentioning
confidence: 99%
“…Magnesium oxychloride cement (MOC) foam concrete (MOCFC) is an air-hardening cementing material formed by mixing magnesium chloride solution (MgCl 2 ) and lightburned magnesia (i.e., active MgO) [37,38]. In practical application, adding caustic dolomite powder into light-burned magnesite powder can reduce the MOCFC production cost.…”
Section: Overview Of This Special Issuementioning
confidence: 99%
“…It can be seen that the compressive strength is inversely related to graphite powder content, decreased by 10.70% when the graphite powder content was raised from 0% to 3%, and decreased by 30.17% when raised to 9%. The compact structure of the hydration products is an essential guarantee for the formation of highstrength cement-based materials [18,19]. First, due to the poor hydrophilicity of graphite powder [20], it is difficult for the hydration products of cement to adhere on its surface, and the interfacial bonding between cement stone and graphite powder is weak [14].…”
Section: Compressive Strength Performancementioning
confidence: 99%